Affectivity as Mediator of the Relation Between Optimism and Quality of Life in Men Who Have Sex with Men with Hiv [Afectividad Como Mediador de la Relación Entre Optimismo y Calidad de Vida en Hombres Que Tienen Sexo Con Hombres Con Vih] - Vera-Villarroel, P; Contreras-Ramirez, D (Elsevier Doyma, 2016)
Background/Objective: Increased life expectancy has made quality of life the primary objective in the care of chronic patients and people living with HIV. It found evidence of the link between optimism, quality of life and well-being. This article aimed to determine whether affectivity in its two dimensions (positive and negative) played a mediating role in the association between optimism and quality of life in men living with HIV. Method: 116 men living with HIV (the average age was 36.8 years (SD=9.06), and the average time from the diagnosis was 8.2 years) responded to three instruments: Life Orientation Test revised version (LOT-R), the Positive and Negative Affect Schedule (PANAS) and the World Health Organization Quality of Life-Bref (WHOQoL-Bref). Results: The results showed that positive affect had no mediating effect, whereas negative affect mediated the relation of optimism with two quality-of-life dimensions (overall quality of life and environment). Conclusion: In conclusion, negative affect was found to participate only partially, acting as a mediating variable. © 2016 Asociación Española de Psicología Conductual